Modernising Waqf through progressive management practices and innovative financing mechanisms: the case of Malaysia - Yussof, Sheila Ainon (2013)
In the last few decades, there have been global concerns on the underutilisation and underdevelopment of Waqf assets, poor governance and weak registry of Waqf lands and a host of other problems which are inhibiting the modernising of Waqf. Conferences have been organised to highlight the weaknesses of the Waqf system in various jurisdictions worldwide, and the pressing need for a reform of their models where they do not comply with Islamic objectives and international standards on good governance. Although various measures have been adopted by governments and private companies to accelerate Waqf developments in their country, it has yet to attain a level of sophistication in relation to accounting, auditing and best management practices, good governance, expertise and accountability of the trustees and managers of Waqf. The traditional Waqf system is currently being revitalized by innovative Waqf instruments and institutions, and confronted by new ways of overcoming old issues, where it can be transformed and depended on by contemporary societies as a more effective tool to economically empower the Muslim ummah and society in general.